Quantifying risk and resource use for a large carnivore in an expanding urban–wildland interface. Issue 2 (29th November 2015) - Moss, Wynne E.; Alldredge, Mathew W.; Pauli, Jonathan N.
Summary: Large carnivores, though globally threatened, are increasingly using developed landscapes. However, most of our knowledge of their ecology is derived from studies in wildland systems; thus, for effective conservation and management, there is a need to understand their behavioural plasticity and risk of mortality in more developed landscapes. We examined cougar Puma concolor foraging ecology and survival in an expanding urban–wildland system in Colorado from 2007 to 2013. For GPS‐collared individuals, we related diet ( n = 41; isotopic analysis) to age–sex class and fine‐scale space use, with regard to levels of habitat development. We also examined how habitat development impacted risk of mortality ( n = 49), using hazards models and records of cougar–human conflict. Cougars obtained 63–82% of assimilated biomass from native herbivores, and adult females consistently showed higher use of native herbivores than other age–sex classes. Individuals using the most highly developed areas obtained approximately 20% more of their diet from alternative prey (synanthropic wildlife and domestic species) than those in the least developed areas. Overall, survival of adult females was higher than adult males. Yet, use of developed areas substantially increased cougar risk of mortality; for every 10% increase in housing density, risk of mortality increased by 6·5%, regardless of sex. Synthesis and applications . Cougars showed flexibility in diet, taking advantage of human‐associated prey items, but had high rates of mortality, suggesting that human tolerance, rather than adaptability, may be the limiting factor for range expansion by cougar and other large carnivores. Thus, large carnivore conservation will not only depend upon adequate prey resources, but also limiting potential conflict resulting from depredation of synanthropic wildlife and domestic animals. Abstract : Cougars showed flexibility in diet, taking advantage of human‐associated prey items, but had high rates of mortality, suggesting that human tolerance, rather than adaptability, may be the limiting factor for range expansion by cougar and other large carnivores. Thus, large carnivore conservation will not only depend upon adequate prey resources, but also limiting potential conflict resulting from depredation of synanthropic wildlife and domestic animals.